Asymmetric wakes in flows past circular cylinders confined in channels. (10th March 2023) - Lu, Wilson; Aljubaili, Daniah; Zahtila, Tony; Chan, Leon; Ooi, Andrew
Abstract: Abstract : In this paper, we investigate the flow past a circular cylinder confined in a channel at a blockage ratio of β =0.7 (the ratio of the cylinder diameter and the channel height) for Reynolds numbers between Re=300 and 3900 using direct numerical simulation (DNS). We show for varying Reynolds numbers a wide range of wake dynamics occur as the spanwise domain length is changed. At a lower Reynolds number of Re=300, a reverse von Kármán wake alongside either a top- or bottom-biased asymmetry was observed at different spanwise locations. The asymmetry was structurally similar the two-dimensional asymmetry studied by prior investigators, and was found to be a result of the confinement effect. Further, wake-jumping between the two intermittent states was present. For larger Reynolds numbers, Re=1000 and 3900, these asymmetric structures were found to become dominant. We also examine the dependence of the asymmetries on the spanwise domain. For small spanwise domains the asymmetries were uniformly orientated across the span. In contrast, for sufficiently large spanwise domains, the asymmetry flips its orientation at different spanwise locations. Comparisons of flow statistics demonstrate good agreement between the different spanwise domains, which suggests the same mechanism maintains the asymmetry in both cases. Further analysis at Re=1000 found the number of times the wake flips is dependent on the initial conditions, with a wake that flips zero (purely asymmetric), two and four times being observed. These structures were also determined to remain stable over time scales of 1000D/U .